Afro-Latinoamérica, 1800-2000 - Andrews, George Reid, 1951-; Torre Cueva, Óscar de la; Andrews, George Reid, 1951- (Madrid : Iberoamericana ; Frankfurt am Main : Vervuert, 2007)
Covering the last two hundred years, this book examines how African-descended people made their way out of slavery and into freedom, and how, once free, they helped build social and political democracy in Latin America.
Includes bibliographical references and index.
Online resource; title from PDF title page (Digitalia, viewed January 5, 2018)
Keywords: Blacks -- Latin America -- History; Racially mixed people -- Latin America -- History; Latin America -- Race relations; Electronic books